2002
DOI: 10.1246/bcsj.75.877
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Corrosion of Stainless Steels with the Presence of Molten Carbonates below 923 K

Abstract: The high-temperature corrosion of stainless steels (SUS316L and SUS310S) in the presence of lithium-potassium eutectic carbonate and lithium-sodium eutectic carbonate has been studied by thermogravimetry and the metal consumption method under a carbon dioxide–oxygen atmosphere in the temperature range of 773–1123 K. Although the corrosion of SUS310S obeyed the parabolic rate law for all reaction conditions, the corrosion of SUS316L significantly depended on the reaction conditions. At or above 923 K, the corro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Parallel corrosion studies on stainless steels indicated that the (Li 0.52 Na 0.48 ) 2 CO 3 electrolyte is slightly less corrosive as compared to the standard one probably due to formation of dense oxide scales with less spallation or cracks [13]. However, a more temperature-sensitive corrosion behavior was reported in the (Li 0.52 Na 0.48 ) 2 CO 3 electrolyte with some accelerated corrosion observed during initial periods at temperatures lower than 600°C [19,20]. This could be explained by assuming a larger dependence of the lithiation reactions on temperature in the (Li 0.52 Na 0.48 ) 2 CO 3 electrolyte.…”
Section: Corrosion Inhibitorsmentioning
confidence: 93%
“…Parallel corrosion studies on stainless steels indicated that the (Li 0.52 Na 0.48 ) 2 CO 3 electrolyte is slightly less corrosive as compared to the standard one probably due to formation of dense oxide scales with less spallation or cracks [13]. However, a more temperature-sensitive corrosion behavior was reported in the (Li 0.52 Na 0.48 ) 2 CO 3 electrolyte with some accelerated corrosion observed during initial periods at temperatures lower than 600°C [19,20]. This could be explained by assuming a larger dependence of the lithiation reactions on temperature in the (Li 0.52 Na 0.48 ) 2 CO 3 electrolyte.…”
Section: Corrosion Inhibitorsmentioning
confidence: 93%
“…The lithiation process is one of the reasons for the electrolyte loss during the operating time of an MCFC [19,20] and, more importantly, this process will change the properties of the scales of stainless steel under thin film of molten carbonate [21][22][23][24]. The corrosion of stainless steel in the cathode compartment or the immersion corrosion will last longer times than thin-film corrosion, so longer testing would be required to study the whole process.…”
Section: Introductionmentioning
confidence: 99%
“…After long test periods, the two-layered structure of the passive scale consists of an external LiFeO 2 layer and an inner Cr-rich oxide layer. The passivity of stainless steels depends on the stability of this inner layer [1,2]. In the case of the high-Cr type 310S steel (ca.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the authors of Refs. [2,4] report that the corrosion of 316L steel becomes highly sensitive on the reaction conditions in the eutectic Li + Na carbonate melt during cell start-up. At temperatures as low as 600 • C this steel seems to become highly susceptible to corrosion damage with a pittinglike attack in high CO 2 gases.…”
Section: Introductionmentioning
confidence: 99%